1997
DOI: 10.1002/(sici)1097-0142(19970801)80:3<351::aid-cncr1>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate analysis of occult lymph node metastasis as a prognostic indicator for patients with squamous cell carcinoma of the oral cavity

Abstract: BACKGROUND The biologic aggressiveness of squamous cell carcinoma of the oral cavity is reflected in its ability to metastasize to regional cervical lymph nodes. Patients with clinically negative cervical lymph nodes are believed to have a good prognosis; however, the prognosis of patients with lymph node metastasis occurring after excision or radiotherapy of the primary tumor is poor. METHODS Univariate and multivariate analyses for occult lymph node metastasis (ONM) in 172 patients with clinically negative c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
84
3
2

Year Published

1998
1998
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(98 citation statements)
references
References 24 publications
9
84
3
2
Order By: Relevance
“…An inverse relationship was also reported by other studies, between lymphocytic infiltrate and nodal disease and overall prognosis [60,61]. …”
Section: Discussionsupporting
confidence: 82%
“…An inverse relationship was also reported by other studies, between lymphocytic infiltrate and nodal disease and overall prognosis [60,61]. …”
Section: Discussionsupporting
confidence: 82%
“…Interestingly, this lack of association has been reported by other studies [26,27]. We do not feel that HOXA1 was sufficiently studied in its role in tumor prognosis in OSCC or other malignancies, however, several studies have reported that lymph node metastasis is the most reliable marker of OSCC patient prognosis [28-30], and our findings showed that the presence of lymph node metastasis significantly correlated with high HOXA1 expression and both were significant prognostic factors for overall survival by multivariate analysis. Since HOXA1 is expressed in a number of cancers, our findings encourage its verification and monitoring in other malignancies.…”
Section: Discussioncontrasting
confidence: 57%
“…The survival rates for patients without lymph node metastasis and those with lymph node metastasis were 94 and 51 per cent, respectively. 24 It is therefore of immense clinical importance to predict the invasive and metastatic potential of oral SCCs.…”
Section: Discussionmentioning
confidence: 99%